2016
DOI: 10.1038/ncomms10816
|View full text |Cite
|
Sign up to set email alerts
|

Structural hot spots for the solubility of globular proteins

Abstract: Natural selection shapes protein solubility to physiological requirements and recombinant applications that require higher protein concentrations are often problematic. This raises the question whether the solubility of natural protein sequences can be improved. We here show an anti-correlation between the number of aggregation prone regions (APRs) in a protein sequence and its solubility, suggesting that mutational suppression of APRs provides a simple strategy to increase protein solubility. We show that mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 52 publications
7
63
0
Order By: Relevance
“…Although this would not eliminate the intrinsic aggregation potential of the molecules, it would at least increase their colloidal stability and hence reduce the initial association required to initiate protein aggregation [36]. In addition, APR disruption could display an interplay with the net charge, as was observed in the engineering of protective antigen [16], where we noticed that the gatekeeper that increased the net charge of the protein also performed best at reducing aggregation. Moreover, for green fluorescent protein, it was previously shown that extreme supercharging is effective at suppressing aggregation, but this is probably not an option for therapeutic molecules due to immunogenicity considerations [36].…”
Section: Resultsmentioning
confidence: 86%
“…Although this would not eliminate the intrinsic aggregation potential of the molecules, it would at least increase their colloidal stability and hence reduce the initial association required to initiate protein aggregation [36]. In addition, APR disruption could display an interplay with the net charge, as was observed in the engineering of protective antigen [16], where we noticed that the gatekeeper that increased the net charge of the protein also performed best at reducing aggregation. Moreover, for green fluorescent protein, it was previously shown that extreme supercharging is effective at suppressing aggregation, but this is probably not an option for therapeutic molecules due to immunogenicity considerations [36].…”
Section: Resultsmentioning
confidence: 86%
“…4). By selectively mutating amino acids at the protein surface, it is possible to tune their solubility while preserving their structure and function (66). This provides a potential means to condense enzymes and thereby elevate their catalytic capability.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the relationship between protein surface domains and the binding affinity of molecules of a drug, protein, or DNA/RNA could aid the design of new molecules to condense enzymes for advanced catalytic performance, and of new therapeutic peptides for selectively targeting certain types of proteins (70). Moreover, protein solubility could be elevated or suppressed by mutating amino acids while preserving bioactivity (66).…”
Section: Discussionmentioning
confidence: 99%
“…Grafting APRs of known amyloidogenic proteins onto proteins that do not aggregate by themselves creates chimeras that recapitulate both the aggregation propensity and aggregate morphology of the donor protein (Ventura et al, 2004;Teng and Eisenberg, 2009). Conversely, it has also been shown that the introduction of point mutations that abolish the aggregation propensity of an APR is sufficient to reduce the aggregation propensity of the entire protein (Ganesan et al, 2016;Marshall et al, 2016). Finally, short peptides solely coding for such APRs are able to induce the aggregation of a full-length protein comprising that APR Khodaparast et al, 2018;Betti et al, 2016).…”
Section: Introductionmentioning
confidence: 99%